Quality culture in advertising agencies and creativity for campaign effectiveness: Analysis of Six Sigma practices - Aarzoo; Ruhi Lal (Social Sciences and Humanities Open)
This study explores the complex relationship between Six Sigma methodologies and the creative processes within advertising agencies, analysing how quality management tools can harmonise with the dynamic and innovative characteristics of the advertising industry. Six Sigma, recognised for its process improvement abilities, encounters difficulties when implemented in fields such as advertising, where creativity is essential. This research aims to investigate the integration of Six Sigma's structured process management with the creative requirements of advertising to improve both quality and campaign performance. This research question explores the integration of Six Sigma into advertising agencies, aiming to enhance process efficiency and campaign outcomes without hindering creativity. The research utilised a qualitative approach involving in-depth interviews with professionals from advertising agencies over four months, specifically from January to April 2024. The study was conducted in three distinct phases: conceptual, narrative, and interpretative. A thorough literature review was performed in the conceptual phase, and the objectives were clearly defined. The narrative phase comprised semi-structured interviews with 40 advertising professionals, which were analysed through phenomenological and deductive methods. The interpretative phase concentrated on pinpointing essential themes concerning the integration of Six Sigma and its influence on creativity. The findings indicated that although Six Sigma enhanced efficiency and minimised errors, its inflexible framework frequently stifled creativity. It was discovered that customising Six Sigma tools can enhance structured creativity, thereby improving the effectiveness of marketing efforts. The study concludes that Six Sigma can be adapted to balance creativity and quality management, suggesting flexible and customised deployment strategies for optimal results. This research adds to the ongoing discussion about integrating Six Sigma in creative industries, encouraging practitioners to explore adaptive strategies that combine efficiency and innovation to enhance advertising performance.